Modifikasi Metode One-Time Pad Dan Chaostic Function Untuk Mengamankan Pesan - Nyata Manalu (TIN: Terapan Informatika Nusantara, 2022)
Information is a collection of data in the form of unified text that is public or confidential. Confidential data is data that contains something or not to be published, because the data is important data. For that, the data needs to be secured. One way to secure the data is to use cryptography. Cryptography is a science that plays an important role in the field of information security. Cryptography has mathematical techniques related to information security aspects, such as data confidentiality and integrity, and authentication. Algorithms in cryptography are divided into two, namely symmetric key algorithms and asymmetric key algorithms. One that is included in the symmetric key algorithm is the one time pad. One Time Pad is a symmetric key algorithm that uses alphabetic substitution by using these letters as plaintext and key letters that have comparable positions. However, along with the development of human science, the weaknesses of the one time pad were found. One way to overcome the weaknesses of the one time pad above is to generate a more random key This study describes how the procedure is carried out to modify the key generation used in the one time pad algorithm. Key generation is done based on the Blum Blum Shub key generator, meaning that the key used in the encryption and decryption process is the key generated based on the chaostic function key generator. can be more optimal in securing data.